A survey of insecticide susceptibility in Plutella xylostella (L.) (Lepidoptera: Yponomeutidae) in the Federal District, Brazil - CASTELO BRANCO,MARINA (2001)
The level of insecticide susceptibility of strains of Plutella xylostella (L.) from the Federal District was evaluated in 1995 and 1996. A homogeneity in acephate and phentoate susceptibility was observed in the surveyed strains. One strain, highly susceptible to Bacillus thuringiensis lost its susceptibility after 10 insecticide sprays in two generations in the field with a 36-fold increase in its LC50. Movements of the pest could have accounted for the observed results.